Dampak Pandemi Covid 19 terhadap Kehidupan Sosial Ekonomi Perempuan - leni Marpelina; Resmiyati Yunus (Jantra., 2021)
This study aims to analyze the impact of the COVID-19 pandemic on the socio economic lives of women. The method used in this research is descriptive analysis, namely by analyzing the impact of the COVID-19 pandemic on women’s socio-economic lives. Data in the form of information were collected from several journals, books, and news related to the impact of the pandemic on women’s lives. The results of this study show that the COVID-19 pandemic has a very significant impact on women’s lives. There are three main impacts, namely the double burden of caring for children and working. Second, the increase in cases of domestic violence, and the third is unequal treatment in the economic sector. This impact gives various life burdens and potentially causes stresses. Mean while, socially, the Indonesian women publicaly as well as domestically have significant roles in supporting and inproving economic and social conditions. Even though they get bigger social risks during the pandemic time, the women could stand in the front line of saving household economic resilience, with various activities that can be done as an effort to affirm the lives.